2017
DOI: 10.1016/j.ejmech.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Aminopurine and aminoquinazoline scaffolds for development of potential dengue virus inhibitors

Abstract: Previous efforts led to dicarboxamide derivatives like 1.3, comprising either an imidazole, pyrazine or fenyl ring as the central scaffold, with many congeners displaying strong inhibitory effects against dengue virus (DENV) in cell-based assays. Following up on some literature reports, the rationale was borne out to preserve the pending groups, now attached to either a 2,6-diaminopurine or 2,4-diaminoquinazoline scaffold. Synthetic efforts turned out less straightforward than expected, but yielded some new de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Although the compound cannot be used for in vivo studies because of it relatively poor pharmacokinetics properties, this work clearly identified an allosteric pocket from DENV that is essentially shared by the ZIKV RdRp and that can now be targeted using rational design. Another interesting NNI compound was also identified by HTS based on an activity assay and on optimisation of identified hits [97,98]. UV-cross-linking of the compound showed that it binds the RdRp domain at the edge of the RNA tunnel blocking the template access and interfering in the transition between the open and close conformations of the protein.…”
Section: Antiviral Strategies Against Ns5mentioning
confidence: 99%
“…Although the compound cannot be used for in vivo studies because of it relatively poor pharmacokinetics properties, this work clearly identified an allosteric pocket from DENV that is essentially shared by the ZIKV RdRp and that can now be targeted using rational design. Another interesting NNI compound was also identified by HTS based on an activity assay and on optimisation of identified hits [97,98]. UV-cross-linking of the compound showed that it binds the RdRp domain at the edge of the RNA tunnel blocking the template access and interfering in the transition between the open and close conformations of the protein.…”
Section: Antiviral Strategies Against Ns5mentioning
confidence: 99%
“…In the past decade, there has been a significant effort to develop small molecules for the treatment of DENV infection, yielding multiple promising candidates with a number of different scaffolds. [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] However, none of these compounds have entered clinical trials for DENV treatment. Interestingly, many of these compounds include common kinase inhibitor scaffolds, such as the oxindole [ 14 ], iso thiazolo[4,3- b ]pyridine [ 15 ] and azaindoles [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Venkatesham et al (2017) investigated two substituted-aminoquinazoline compounds 100 and 111 ( Fig. 25 ) for the anti-DENV activities [ 169 ]. The outcomes showed that compound 110 posed the maximum inhibition among the other synthesized aminoquinazoline derivatives (EC 50 and SI value of 2.6 μM and 2, respectively).…”
Section: Nitrogen ( N ) - Conta...mentioning
confidence: 99%